THE ROLE AND SIGNIFICANCE OF PHYSICAL ACTIVITY ON THE HUMAN BODY - Турсумбаев, Азиз; Макарова, Елена; Шарипова, Гульнара (SWorldJournal, 2020)
Physical exercise is a necessary component in self-improvement, as a means of maintaining health and performance. The effect of a complex of physical exercises on the body improves its physical condition, the activity of the cardiovascular system and the